COVID-19 and the Cardiovascular System. Issue 4 (October 2020) - Veer, Manik; Kumar, Aarthi Madhana; Ivanova, Valentyna
Abstract : COVID-19, a symptom complex of respiratory failure induced by a highly infectious pathogen, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has been classified as a pandemic. As of April 15, 2020, there have been 2 million people diagnosed with the viral infection and 130 000 deaths globally. It is highly likely that the number of infections is underrepresented secondary to variations in testing and reporting strategies globally. In this short review, we aim to summarize the current understanding of SARS-CoV-2 as it pertains to cardiovascular disease. We discuss the basis of cardiac pathophysiology and address some of the clinical scenarios that cardiovascular physicians may face. We introduce the concept of conservative management of acute coronary syndromes and address some complications such as myocarditis, heart failure, and cardiac arrhythmias that may be relevant for the management of patients presenting with COVID-19.